Apakah Post-Truth Berbasis Ideologi Membahayakan Demokrasi: Perspektif Penyebaran Fakta Di Media Sosial - Sharine, Sondang; Sitorus, Fitzerald Kennedy (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The “post-truth” phenomenon that shakes the foundations of democracy by prioritizing emotional and ideological narratives over objective facts, especially in the context of social media and ideology, threatens healthy political processes and participation in society in political decision making. The aim of this research is to understand the impact of ideology-based post-truth on the stability and integrity of democracy. The research methods used in this article are based on a comprehensive literature review. The results of this research are that ideology-based post-truth poses a serious threat to the health of democracy. This phenomenon not only creates deeper political polarization and results in the spread of damaging misinformation, but also adds to the foundations of democracy such as trust in institutions, political stability, and freedom of thought and expression. The public must understand that when ideology dominates the political narrative and objective facts are ignored, democracy becomes vulnerable to manipulation and power manipulation.